Stress and career aspirations: a longitudinal study with medical students - Picker-Roesch, Clara; Lang, Jessica (Frontiers in Psychology, 2024)
Background: The psychological well-being of medical students has often been studied in relation to various factors and typically exhibits poorer scores than comparable student groups. This diminished well-being can have far-reaching implications, like impact on career or academic engagement. While there are some studies on specialty choice or academic performance few studies have examined the effects of stress at the beginning of medical school on career ambitions and the associated interest in research. Given the anticipated future shortage of healthcare professionals and the goal of gender equality in higher positions, it is crucial to examine this relationship as early as medical education. The question arises whether medical education and the demands of studying influence the career ambitions of different student groups.Method: As part of a longitudinal survey, students from a medical cohort are surveyed over three consecutive years. A total of 297 students participated in the surveys, of which 66.4% were women. Stress experiences during medical school and career aspirations are assessed and analyzed using Generalized Estimating Equation (GEE) modeling.The results indicate that early academic stress is a negative predictor of the career ambitions of medical students (B = 1.637; p = 0.009). Also, female students report lower career goals than male students (B = 1.168; p = 0.018). In addition, gender moderates the impact of stress on career ambitions (p = 0.046). Finally, stress levels are highest when starting the medical program (p = 0.022) and decrease over time. Discussion: Stress during the initial medical training impedes students to pursue higher career ambitions. Future research as well as medical programs need to elaborate more on and consider structural stress prevention interventions in order to promote well-being and strengthen also scientific career goals at an early stage, specifically for female students.